Pemanfaatan Data Penginderaan Jauh untuk Pemetaan Potensi Air Tanah di Kota Denpasar dan Badung - Minerva, Renata Clarice; Suyarto, R.; Wiyanti, Wiyanti (Nandur; Vol 3 No 3 (2023), 2023)
Groundwater need is always increasing due to population growth, climate change, economic growth, and uneven water distribution, especially in the densely populated areas like Denpasar and Badung, which also has a large area of built-up land. Excessive and continuos use of groundwater can cause a decrease in its quality and quantity. Such conditions make the research of groundwater potential is important to do. The purpose of this research is to determine the distribution of groundwater potential in the Denpasar and Badung regions and compare the results with the actual conditions. The methods that are used in this research are the calculation of vegetation index, rainfall data, and DEM data using Remote Sensing. This research results in the form of maps of rainfall, slope, elevation, and maps of NDMI, NDWI, SAVI, GNDVI, NDVI, BSI, dan NDBI. The research showed that groundwater potential in the location is divided into five classes, which are Very low, low, medium, high, and very high. Areas with very low groundwater potential are dominated by West Denpasar, North Denpasar, and parts of South Denpasar. the low class dominates the Kuta area, medium class is spread throughout the region, high class dominates the North Kuta area, while the very high class dominates the lower part of South Denpasar and some parts of North Kuta.